Improvement of fermentation profile and structural carbohydrate compositions in mixed silages ensiled with fibrolytic enzymes, molasses and Lactobacillus plantarum MTD-1 - Siran Wang (Italian Journal of Animal Science, 2019)
In order to enhance the feed’s nutritive value and utilisation efficiency of local straws in Tibet, hulless-barley straw was conserved as silage by mixing with tall fescue and adding the tested additives and their combination. In experiment 1, hulless-barley straw was ensiled with four levels of tall fescue (0, 20, 40 or 60 of fresh weight, FW) in laboratory silos (1 L) for 60 days. The results suggested that 40% hulless-barley straw inclusion of 60% tall fescue was proper for further study. In experiment 2, a mixture of hulless-barley straw and tall fescue (40/60) were treated with (1) no additive (control), (2) fibrolytic enzymes (E, 0.1% FW), (3) molasses (M, 4% FW), (4) Lactobacillus plantarum MTD-1 (Lp, 106 cfu g−1 FW), (5) E + Lp and (6) M + Lp, respectively. Silos were opened after 7, 24, 45 and 60 days of ensiling respectively. The fermentation quality and structural carbohydrates were analysed. After 60 days of ensiling, all the additives except fibrolytic enzymes increased the lactic acid contents, and decreased the pH, ammonia nitrogen and butyric acid contents. All the treated silages had lower neutral detergent fibre, acid detergent fibre, hemicellulose and cellulose contents than that of control, especially in E + Lp and M + Lp treated silages. In conclusion, application of L. plantarum together with fibrolytic enzymes or molasses could further improve the fermentation quality and structural carbohydrate compositions in comparison with using each of the three additives alone.Highlights Enhancing the utilisation efficiency of local straws by mixed silage. Improving the feed’s nutritive value by reducing the crude fibre contents.